Chinese Media, Kenyan Lives: An Ethnographic Inquiry into CCTV Africa's Head Offices - Melissa Lefkowitz (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
This paper examines how Kenyan, Chinese, and other international media professionals navigate the everyday production of media at CCTV Africa's head offices in Nairobi, Kenya. It provides a portrait of the multifaceted experiences of CCTV Africa staff, including their narratives of joining CCTV, producing news content, navigating relationships with managerial staff, and planning for the future. While CCTV Africa's employees are, on average, satisfied with CCTV Africa's work environment and conditions, problematic areas regarding safety, interpersonal relationships, and training deserve further consideration and investigation.
Keywords: 330